2019
DOI: 10.1186/s12937-019-0492-9
|View full text |Cite
|
Sign up to set email alerts
|

Does the inflammatory potential of diet affect disease activity in patients with inflammatory bowel disease?

Abstract: BackgroundDiet is an important modulator of inflammation, which is associated with inflammatory bowel disease (IBD). In this study, we examined whether the inflammatory properties of diets are associated with disease activity in patients with IBD.MethodsA cross-sectional study was conducted on 143 IBD patients, including 32 patients with Crohn’s disease (CD) and 111 patients with ulcerative colitis (UC). Dietary intakes were assessed by a valid 168-item food frequency questionnaire (FFQ). The inflammatory pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 37 publications
4
29
1
1
Order By: Relevance
“…An analysis of three large prospective cohorts showed that dietary patterns with high inflammatory potential were associated with an increased risk of developing CD, but not UC, though they used a slightly different inflammatory index [2]. In contrast to our results, a recently published cross-sectional study in Iranian patients with an established IBD diagnosis did not find an association between the inflammatory potential of diet and disease activity [22]. The null finding in the Iranian patients might be due to the small sample size (n = 143), especially the small number of participants with CD (n = 32), as compared to 178 CD patients in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…An analysis of three large prospective cohorts showed that dietary patterns with high inflammatory potential were associated with an increased risk of developing CD, but not UC, though they used a slightly different inflammatory index [2]. In contrast to our results, a recently published cross-sectional study in Iranian patients with an established IBD diagnosis did not find an association between the inflammatory potential of diet and disease activity [22]. The null finding in the Iranian patients might be due to the small sample size (n = 143), especially the small number of participants with CD (n = 32), as compared to 178 CD patients in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies reported the educational level of participants. Of the seven studies that reported the education level, this ranged from 39.6% to 80.8% of participants possessing a college level of education 26,59 …”
Section: Resultsmentioning
confidence: 99%
“…The most frequently used tool was a 3‐day food record (eight studies 42,47,52,53,55,60‐62 ), followed by a 7‐day food record (five studies 32,40,44,50,54 ). Various food frequency questionnaires were used which captured food frequency data over 24 hours (six studies 30,33,41,51,56,61 ), 1 week (2 studies 27,28 ), 1 month (three studies 23,36,37 ), 3 months (one study 58 ) and 1 year (two studies 26,63 ) periods and ranged from 86, 57 99, 43 110, 23,48 150, 38 18 59 or 630 food items 22 . Three studies used multiple methods of a food recall and food frequency questionnaire 32,51,62 .…”
Section: Resultsmentioning
confidence: 99%
“…There have also been some studies examining the effect of the inflammatory potential of the diet, as measured by a score, on gut inflammation and disease activity in patients already diagnosed with IBD, but both positive and null relationships have been reported [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%